Grammatical reconstruction the Sogeram languages of New Guinea - Daniels, Don (Studies in Language Change [SLC] ;, 2020)
There is still widespread disagreement among historical linguists about how, or whether, syntactic reconstruction can be done. This book presents a comprehensive methodology for syntactic reconstruction, grounded in a constructional understanding of language. The author then uses that methodology to reconstruct Proto-Sogeram, the ancestor to ten languages in Papua New Guinea. Chapters are devoted to phonology, lexicon, verbal morphosyntax, nominal morphosyntax, and syntactic constructions. The work culminates in a sketch of Proto-Sogeram grammar. Based largely on the author's original fieldwork, this is an innovative application of a novel methodology to new data, and the most complete reconstruction of a Papuan proto-language to date. It will be of interest to scholars of language change, language reconstruction, typology, and Papuan languages.